(In)variability in the Samoan syntax/prosody interface and consequences for syntactic parsing. Issue 1 (18th October 2017) - Yu, Kristine M.; Stabler, Edward P.
Abstract : While it has long been clear that prosody should be part of the grammar influencing the action of the syntactic parser, how to bring prosody into computational models of syntactic parsing has remained unclear. The challenge is that prosodic information in the speech signal is the result of the interaction of a multitude of conditioning factors. From this output, how can we factor out the contribution of syntax to conditioning prosodic events? And if we are able to do that factorization and define a production model from the syntactic grammar to a prosodified utterance, how can we then define a comprehension model based on that production model? In this case study of the Samoan morphosyntax-prosody interface, we show how to factor out the influence of syntax on prosody in empirical work and confirm there is invariable morphosyntactic conditioning of high edge tones. Then, we show how this invariability can be precisely characterized and used by a parsing model that factors the various influences of morphosyntax on tonal events. We expect that models of these kinds can be extended to more comprehensive perspectives on Samoan and to languages where the syntax/prosody coupling is more complex.